Tindak Tutur Ekspresif terhadap Pelayanan Kesehatan di Rumah Sakit Islam Sultan Agung Semarang - Astuti, Sri Puji (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Hospital service satisfaction is a dream for all patients, patient families, and visitors  of the hospital. The reality in the place shows that there are patients, patient families, and visitors who are satisfied with the hospital services and some are not. Based on the facts in this paper is discussed what the functions of expressive speech acts of health services at Sultan Agung Islamic Hospital Semarang. This research data was the fragment of discourse containing expressive speech act of patient or patient's family, and the visitors in health service review Sultan Agung Islamic Hospital Semarang through facebook. Collecting data is done by using observation method. Data were analyzed by using pagmatic theory. The results of research showed that the function of expressive speech act used by the author of reviewing Sultan Agung Islamic Hospital Semarang, there are four kinds. Those are saying thank you, criticizing, complaining, and praising.